On asymptotic decompositions of o-solutions in the theory of quasilinear systems of difference equations - Kostin, A. V.; Skrypnik, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider a quasilinear system of difference equations with certain conditions. We prove that there exists a formal partial o-solution of this system in the form of functional series of special type. We also prove a theorem on the asymptotic behavior of this solution.